Post-exercise cold water immersion: Effect on core temperature and melatonin responses - Robey, E.; Dawson, B.; Halson, S.; Goodman, C.; Gregson, W.; Eastwood, Peter (2013)
To study the effect of post-exercise cold water immersion (CWI) on core temperature and melatonin responses, 10 male cyclists completed two evening (~1800 hours) cycling trials followed by a 15-min CWI (14 C) or warm water immersion (WWI; 34 C), and were then monitored for 90 min post-immersion. The exercise trial involved 15 min at 75 % peak power, followed by a 15 min time trial. Core (rectal) temperature was not different between the two conditions pre-exercise (~37.4 C), post-exercise (~39 C) or immediately post-immersion (~37.7 C), but was significantly (p < 0.05) below pre-exercise levels at 60 and 90 min post-immersion in both conditions. Core temperature was significantly lower after CWI than WWI at 30 min (36.84 ± 0.24 vs. 37.42 ± 0.40 C, p < 0.05) and 90 min (36.64 ± 0.24 vs. 36.95 ± 0.43 C, p < 0.05) post-immersion. Salivary melatonin levels significantly increased (p < 0.05) from post-exercise (~5 pM) to 90 min post-immersion (~8.3 pM), but were not different between conditions. At 30 and 90 min post-immersion heart rate was significantly lower (~5-10 bpm, p < 0.01) after CWI than WWI. These results show that undertaking either CWI or WWI post-exercise in the evening lowers core temperature below baseline for at least 90 min; however, the magnitude of decrease is significantly greater following CWI. The usual evening increase in melatonin is unaffected by exercise or post-exercise water immersion undertaken between ~1800 and ~2000 hours. © 2012 Springer-Verlag.